The impact of lost therapeutic benefit (LTB) in high-risk hypertensive patients: 2-Year follow-up data from the australian REACH registry - Ademi, Z.; Huq, M.; Liew, D.; Steg, P.; Bhatt, D.; Nelson, M.; Reid, Christopher (2013)
Objective: The aim of the study is to determine the extent of lost therapeutic benefit (LTB) in the hypertensive patients, and to determine the relationship between the presence of LTB and clinical outcomes. Methods: Prospective-cohort study of n = 2856 patients with or at high risk of atherothrombosis. LTB was calculated as the proportion of patients receiving blood pressure medication who were not attaining guideline blood pressure (BP) control targets (<140/90 mmHg). Logistic regression analysis was performed to identify predictors of LTB at baseline, and propensity score matching (PSM) was undertaken to estimate the treatment effects by matching case LTB and control non-LTB cohorts based on the nearest neighbor matching. Results: Of the total sample of 2856, 45.6% had uncontrolled BP, and LTB was present in 46.7% patients. The likelihood of LTB was less in males (OR = 0.78 [95% CI; 0.64-0.97]), and those with a previous myocardial infarction (OR = 0.66 [0.53-0.81]) or heart failure (OR = 0.58 [0.42-0.82]). LTB was more common in those with diabetes (OR = 1.44 [1.16-1.79]), aged >65 years (OR = 1.36 [1.06-1.75]) and having an ABI < 0.09 in either leg at rest (OR = 1.30 [1.02-1.75]). Following PSM, the combination of ischemic events (55-64 age category) was more likely to occur in the LTB compared with non-LTB group (4.38% and 0.68%, respectively [P = 0.046]). Conclusion: Presence of HF, previous MI and being male decreased the likelihood of LTB, while presence of diabetes, age > 65 and ABI < 0.09 increased the risk of LTB. Patients with LTB in age category 55-64 had higher incidence of vascular events compared with those with non-LTB. © 2013 John Wiley & Sons Ltd.